Improving Students' Initial Reading Skills Through Canva Application-Based Picture Word Card Media - Alfiyah Rohmah Atstsaniyah; Arif Widagdo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Low reading ability in students can have a long-term negative impact on the learning process. Inadequate reading skills will affect the achievement of overall student learning outcomes. This research aims to develop a picture word card media based on the Canva application that is valid, effective, and practical to improve the initial reading skills of grade I students. The subject of the research at the implementation stage is grade I students of elementary school. Media validation is carried out by media experts, material experts, and linguists. Data collection is carried out through tests, interviews, observations, questionnaires, and documentation, with questionnaires as data collection instruments. The data was analyzed descriptively, both qualitatively and quantitatively. The results of the study show that the Canva application-based picture card media developed is feasible to use based on assessments from experts and positive responses from teachers and students. The conclusion of this study is that the media can improve students' reading skills and has the potential to be used in initial reading learning.